Reconfigurable Real Time Signal Capturing through FPGA - Bhagat Kumar, B. H. K.; Khadar Bhasha, S. (Asian Journal of Engineering and Applied Technology, 2017)
Today all communication systems are prototyped on FPGAs before sending them for ASIC backend and fabrication. On other side the FPGAs with million gate logic densities and embedded block RAMs allowed the high speed signal capturing and storage for real time analysis. Performing various functions on the captured data allows high speed spectrum analysis. These two allow the prototyping of complex communication system on FPGA and real time analysis of implemented blocks. There are several types of interface methods possible to communicate the FPGA with a computer.. In this paper novel techniques are implemented for capturing and analyzing the signals of any design on FPGA with configurable UART interface. VHDL will be used for implementation of necessary modules such as block memory, capture FSM, triggering logic and UART interface. Necessary scripts will be developed to generate the synthesizable VHDL code as per the requirements of user. The captured data will be sent to PC using UART. Xilinx ISE will be used for systhesis and performance analysis.